Assessment of Scientific Literacy Skills of College of Education Students in Nigeria - Kola, Aina, Jacob; Opeyemi, Abdulrahman Abdulgafar; Olu, Ayodele Michael (American Journal of Social Sciences and Humanities, 2020)
The study randomly sampled one hundred and thirty-three integrated science students of a College of Education to assess their scientific literacy skills. The study was a survey design method. Data for the study was obtained through both qualitative and quantitative approaches. The research instruments were the Scientific Literacy Skills Test (SLST) and a semi-structured interview protocol. Eight skills were investigated which were grouped into three clusters. The study provided answers to three research questions. Data obtained were analyzed using the statistical tools of the t-test, descriptive statistics and thematic coding. Findings showed that students did not possess the scientific literacy skills required for them to function effectively after graduation in society. Besides, male students possessed more scientific literacy skills than their female counterparts in all three clusters of skills examined. Also, finding revealed that students used scientific literacy skills to solve real-life problems such as taking decisions and solving security problems. The paper made some recommendations for further study to enhance students’ scientific literacy skills.